ANALISIS FILE UPLOAD VULNERABILITY DANPENCEGAHAN DENGAN FILE CONTENT VALIDATION - Jose Alnevo Theora, (2021)
File Upload Vulnerability is a vulnerability found on a website caused by the imperfect writing of program code. Wherewith these vulnerabilities, it is possible for people who do not have the authority to upload malicious files such as backdoors into the system or website server. The purpose of this study is to be able to find out things related to File Upload Vulnerability, Can create website-based applications that can prevent backdoor entry into the system, Can make references for related research. So to prevent this, it is necessary to prevent File Upload Vulnerability by doing File Content Validation where this method will select files to be uploaded to the website. Where the file filtering process is done by filtering the file extension, and then the contents of the file will be checked, whether it contains a string that is usually found in the backdoor. If the file is indicated as a backdoor because of a match in the string, then the file will not be able to enter or uploaded, and if the file is safe, then the file will be able to enter or be uploaded to the system. From the results of the File Content validation experiment by uploading 150 files, the results obtained are, as many as 30 executable files and 6 PHP backdoor files cannot enter the server that has been provided. So using File Content Validation can prevent the entry of executable files and PHP backdoor files into the server.